Web services on rails - Marshall, Kevin (O'Reilly, 2006)
This PDF will show you how your small business or enterprise can publish its APIs (application programming interface) to a developer community just like the behemoths of the Internet--Google, Yahoo!, eBay, and Amazon. These giants already offer their APIs to other programmers and allow for add-on services and mash-ups to develop from them--but until recently, the capability for most enterprises to do the same was limited by a myriad of competing standards and a lack of easy-to-use tools to accomplish the task. Ruby on Rails levels the playing field for companies by simplifying the process.